Improving the public's willingness to purchase near-expired food to reduce food waste: The case of milk products in China - Shujun Cheng; Xuanhao Shi; Yanjun Ren; Minjuan Zhao (Agricultural Economics (Zemědělská ekonomika), 2025)
The near-expired food (NEF) is a significant opportunity to reduce food waste, while consumers often associate NEF with safety issues, which results in a large amount of safe and healthy food being wasted globally. This research focuses on food date labelling (FDL) and explores how consumers' label cognition impacts their willingness to purchase NEF. Using a random sampling method online, we obtain 2 113 valid samples from China and conduct an information intervention 'quasi-natural experiment' to obtain participants' FDL cognition and willingness to purchase the near-expired milk (NEM) before and after the intervention and evaluate the impact of the intervention through the differences-in-differences model. The results show that consumers' initial purchase willingness for NEM is low, and their FDL cognition has a positive effect, especially in Eastern China and higher education consumers. Information intervention increases consumers' willingness to purchase NEM by changing their label cognition, and the intervention has a more pronounced impact among older, male, and higher education consumers. Considering the pressure on resources and the environment caused by food waste has become an impediment to sustainable development, the findings expand the application of the Knowledge, Attitude, and Practice (K-A-P) theory in the NEF field and clearly reveal the important role of eliminating consumer prejudice of FDL in reducing food waste to achieve the United Nations Sustainable Development Goal 12.3 'Halve food waste.'
Keywords: 630; difference-in-differences; experimental economics; food date labelling; food industry; food waste